Pengaruh Pelaksaaan Good Corporate Governance, Corporate Social Responsibility, kinerja keuangan terhadap nilai perusahan perusahaan food and beverages di Bursa Efek Indonesia selama periode 2009-2013 - Richmayati, Maya (UP2M SEKOLAH TINGGI ILMU EKONOMI GALILEO, 2018)
This research to identify the influence of good corporate governance (general meeting of shareholders, the board of independent commissioner, board of directors, audit committee), corporate social responsibility, financial performance (profitability ratio of net profit margin and return on investment) of the value of the company. This research uses secondary data from the 2009-2013 annual reports of public companies listed in Indonesia Stock Exchange. Research using 13 samples of food and beverages company. Through multiple linear regression analysis approach, the general meeting of shareholders, the board of independent commissioners, the board of directors have a negative and insignificant effect on the financial performance and corporate value. The audit committee has a positive and significant impact on firm value and does not have any impact on the financial performance. Financial performance is proxied by the net profit margin has no significant negative effect on firm value and financial performance is proxied by the return on investment has no significant positive effect on firm value.